Interstitial Cystitis-Critical Assessment of Current Treatment and Opportunities for Nanodelivery - Asif, Afzal Haq; Nair, Anroop; Aldhubiab, Bandar; Nagaraja, Sreeharsha; Meravanige, Girish; Asdaq, Syed Mohammed Basheeruddin; Anwer, Md. Khalid; Shariff, Arshia; Noor, Syed Dawood (Indian Journal of Pharmaceutical Education and Research, 2022)
The characteristic feature of Interstitial cystitis (IC) or bladder pain syndrome is augmented, pressure, or inconvenience in the suprapubic or bladder region. The causative factors for IC are not completely understood however certain underlying disease condition may trigger the pain. The therapy is aimed to provide symptomatic relief, and therefore, the treatment protocols have been established based on experience. Intravesical delivery of drugs has been well explored and found to be most effective in minimizing the symptoms of IC without systemic adverse events. However, the efficacy of drug absorption is limited by the bladder wall permeability and poor absorption of the instilled drugs. The intravesical approach should be coupled with novel nanocarriers such as nanoparticles or liposomes to overcome these limitations. Nanoparticles can easily cross the bladder permeability barrier and enhance the drug retention time in the bladder, making the delivery efficient and promising. This review addresses the current IC management strategies, new potential therapeutic agents of natural origin, and various drugs undergoing clinical trials by different routes of administration.
Keywords: IC; Bladder pain syndrome; Bladder permeability barrier; Intravesical delivery; Nanotherapeutics